1983
DOI: 10.1177/096032718300200204
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobinuric Renal Failure due to Drug-induced Rhabdomyolysis

Abstract: 1 Two cases of drug-induced rhabdomyolysis, one of them presenting with acute myoglobinuric renal failure are described. 2 The pathogenesis of rhabdomyolysis and renal failure in our cases is discussed with reference to work published by other authors. 3 Whereas there seems to be obvious evidence for direct toxic drug-muscle interaction, the mechanism for the development of myoglobinuric renal failure remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Rhabdomyolysis induced by doxylamine overdose was first reported in 1983, 2 and Koppel et al 3 described complications including rhabdomyolysis in 1987. It has been reported that the incidence of rhabdomyolysis induced by doxylamine overdose was 5-57%, and that rhabdomyolysis can progress to acute renal failure.…”
mentioning
confidence: 99%
“…Rhabdomyolysis induced by doxylamine overdose was first reported in 1983, 2 and Koppel et al 3 described complications including rhabdomyolysis in 1987. It has been reported that the incidence of rhabdomyolysis induced by doxylamine overdose was 5-57%, and that rhabdomyolysis can progress to acute renal failure.…”
mentioning
confidence: 99%
“…Anticholinergic symptoms present in these cases included tachycardia, mydriasis, and dry skin and mucous membranes. Anticholinergic symptoms were not reported in the case by Hampel et al (71). The dose ingested in the case reported by Viertel et al (66) was 1500 mg; the amounts ingested in the remaining cases were not reported.…”
Section: Diphenhydramine: Rhabdomyolysismentioning
confidence: 82%
“…The temperatures on admission were documented in three of the other four cases and were reported to be 37.6, 37.1, and 37.2°C) (31,56). Four of the five cases were adults (50,56,71) and one was a 23-month-old (31). Anticholinergic symptoms present in these cases included tachycardia, mydriasis, and dry skin and mucous membranes.…”
Section: Diphenhydramine: Rhabdomyolysismentioning
confidence: 87%
See 1 more Smart Citation
“…Although it is usually seen in alcohol abusers, seizures, and/or crush injuries [2], the syndrome has rarely been reported following status asth maticus. Some drugs, such as theophylline [3][4][5][6], cortico steroid [7][8][9][10], and other drugs [11] induce skeletal mus cle injury. We report here a case of rhabdomyolysis fol lowing status asthmaticus.…”
Section: Introductionmentioning
confidence: 99%